Apropiación territorial y construcción de identidad colectiva frente al despojo de recursos. El caso del Geoparque Mundial Mixteca Alta, Oaxaca, México - Orozco López, Efrén (Empiria. Revista de metodología de ciencias sociales, 2020)
Una discusión reciente en México es la posesión territorial. Este artículo comprende cuatro apartados que discuten tal fenómeno. El primero refiere al despojo como proceso histórico que se da por la disputa de recursos naturales, se ejemplifican dos casos de México y se plantean a los geoparques mundiales como alternativas de apropiación territorial de comunidades originarias. El segundo analiza fundamentos de los geoparques, y su situación en Latinoamérica, especificando al Geoparque Mundial Mixteca Alta (GMA). El tercero aborda la Educación Popular como paradigma de análisis, enfatizando al taller como herramienta de reflexión y acción en temas como la defensa del territorio. finalmente se da cuenta de dos talleres realizados a guías del GMA y los resultados referentes a la apropiación territorial. An actual discussion in Mexico has been the possession of land by the indigenous communities. The article is organized into four sections. The first refers to territorial evictions as a relevant historical process in Latin America due to the dispute over natural resources. In this same section the attention is focused in two cases of the activities developed in two mexican indigenous lands and the importance of the existence of geoparks as an alternative to land possession. The second section analyzes the characteristics of geoparks, their situation in Latin America, particularly in the case of the Mixtec World Geopark (GMA) in Mexico. The third part refers to methodologies that are based on Popular Education. It emphasizes the implementation of workshops as a tool that intends to generate reflection and action on issues such as the defense of the communal land. The final section represents the testimonies of two workshops conducted with GMA guides and their results regarding territorial management and property.